Normative data for the Brief Cognitive Screening Battery stratified by age and education - Mônica Sanches Yassuda; Henrique Salmazo da Silva; Thais Bento Lima-Silva; Meire Cachioni; Deusivania Vieira da Silva Falcão; Andrea Lopes; Samila Sathler Tavares Batistoni; Anita Liberalesso Neri (Dementia & Neuropsychologia)
ABSTRACT Introduction: Diagnosing neurocognitive disorders is challenging in low-educated individuals. Objective: To report normative data for the Brief Cognitive Screening Battery (BCSB) and to assess the association of age and education with performance on the BCSB in 240 community-dwelling elderly from Ermelino Matarazzo, São Paulo city. Methods: The inclusion criteria were scoring above the education-adjusted cut-off points on the Mini-Mental State Examination (MMSE) and below six points on the Geriatric Depression Scale (GDS). Results: Age was associated with performance on the Naming, Incidental Memory, Verbal Fluency, Clock Drawing Test, Delayed Recall and Recognition subtests. Education was associated with performance on Naming, Recognition, Verbal Fluency and the Clock Drawing Test. Conclusion: The normative values reported are relevant for diagnosing neurocognitive disorders in low-educated elderly.